A case study on teacher training needs in the Madrid bilingual project - Pilar Cabezuelo Gutierrez; Raquel Fernández Fernández (Universidad de La Sabana, 2014)
Bilingual education programmes are increasingly important in non-English speaking countries as part of the necessary adaptation demanded by the "White Paper on Education and Training" (1995) in both educational and social fields thus becoming a key element in any long-term academic planning. The present case study analyses the opinion of 17 primary teachers in the bilingual programme with regard to the language and methodological training received during the eight years of implementation. The study also aims to gather feedback from the teachers in order to define potential teacher training improvement opportunities. This study stems from two previous studies conducted by Fernández et al (2005) and Fernández and Halbach (2011) as the basis of understanding how the teachers feel about their initial training, its application to real-life classes and their current/future needs in this area. After carefully analysing all the results, it seems that the situation within teacher training has improved over the years. However, there is still much work to be done in order to make this project progress successfully.